Autotaxin, a secreted lysophospholipase D, as a promising therapeutic target in chronic inflammation and cancer. (April 2015) - Barbayianni, Efrosini; Kaffe, Eleanna; Aidinis, Vassilis; Kokotos, George
Abstract: Autotaxin (ATX) is a member of the nucleotide pyrophosphatase/phosphodiesterase family of ectoenzymes that hydrolyzes phosphodiester bonds of various nucleotides. It possesses lysophospholipase D activity, catalyzing the hydrolysis of lysophosphatidylcholine into lysophosphatidic acid (LPA), and it is considered the major LPA-producing enzyme in the circulation. LPA is a bioactive phospholipid with diverse functions in almost every mammalian cell type, which exerts its action through binding to specific G protein-coupled receptors and stimulates various cellular functions, including migration, proliferation and survival. As a consequence, both ATX and LPA have attracted the interest of researchers, in an effort to understand their roles in physiology and pathophysiology. The present review article aims to summarize the existing knowledge as to the implications of ATX in chronic inflammatory diseases and cancer and to highlight the low molecular weight compounds, which have been developed as leads for the discovery of novel medicines to treat inflammatory diseases and cancer.